As Media Augmented Reality Promotion of College with Marker Logo in Brochure (International Journal of Scientific Research and Management (IJSRM), 2017)
Innovation Augmented Reality (AR) is widely used in various fields of media presentation of information such as the interactive learning media , marketing, supply and sale of an organization, service, or product. Colleges still use the brochure as a media campaign, but with the AR, the promotion of existing facilities can be presented in an interactive form. Information can be presented in the form of 3D animation, which can be accessed on Android smartphones and tablets, the goal is to attract students to the college offered. The facilities are presented in the form of virtual 3D is a map and the building, a library, classrooms, and laboratories. A Marker used to identify the camera is a college logo on brochures which combined with red and blue lines.